2019
DOI: 10.1063/1.5098959
|View full text |Cite
|
Sign up to set email alerts
|

Probing micron-scale distributed contortions via a twisted multicore optical fiber

Abstract: Continuous measurement of small length scale contortions along an arbitrary path is a highly relevant goal within many branches of engineering and technology. An optical fiber-where the probing light propagates within a confined and shielded region-presents an ideal platform for developing the distributed contortion-sensors. In the past, significant progress has been made in developing optical fiber sensors, but a robust and high-resolution distributed contortion-sensor has not been reported in detail. Here, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…Lengths in excess of 1 km are readily fabricated into cables and can provide information about temperature, strain, and acoustics without the requirement for electrical connections, and with the possibility of resistance to harsh environmental conditions in various structures. Examples of sensing systems include distributed temperature (Gifford et al, 2005;Sancho et al, 2013), strain (Froggatt and Moore, 1998) and acoustic sensing (Daley et al, 2013;Kirkendall et al, 2007;Diamandi et al, 2019), as well as sensing of bend and shape (Gander et al, 2000;Duncan et al, 2007;Ahmad et al, 2019). A critical aspect of such systems is that they rely on backscattering of light propagating in the core of an optical fiber, usually in single-mode operation.…”
Section: Introductionmentioning
confidence: 99%
“…Lengths in excess of 1 km are readily fabricated into cables and can provide information about temperature, strain, and acoustics without the requirement for electrical connections, and with the possibility of resistance to harsh environmental conditions in various structures. Examples of sensing systems include distributed temperature (Gifford et al, 2005;Sancho et al, 2013), strain (Froggatt and Moore, 1998) and acoustic sensing (Daley et al, 2013;Kirkendall et al, 2007;Diamandi et al, 2019), as well as sensing of bend and shape (Gander et al, 2000;Duncan et al, 2007;Ahmad et al, 2019). A critical aspect of such systems is that they rely on backscattering of light propagating in the core of an optical fiber, usually in single-mode operation.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to MMF fiber imaging applications, many fiber-based sensors of bend, position, twist and displacement have been demonstrated. In the most general case, it has been shown that the entire three-dimensional shape of a fiber can be reconstructed using twisted multicore fibers and optical frequency domain reflectometry E-mail: tkremp@ofsoptics.com (OFDR) [13][14][15] . Such fiber shape reconstruction can be used in sensors and encoders for three-dimensional motion control applications in fields ranging from robotics to medical procedures.…”
Section: Introductionmentioning
confidence: 99%
“…The interference between two supermodes excited in the MCF has been used to obtain an interferometric strain sensor. Multi-parameter sensors for rotation and bending are reported in the literature as well [ 9 , 10 , 11 , 12 , 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%